2001
DOI: 10.1093/humupd/7.2.161
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of uterine malformations and hysteroscopic treatment results

Abstract: Uterine malformations consist of a group of miscellaneous congenital anomalies of the female genital system. Their mean prevalence in the general population and in the population of fertile women is approximately 4.3%, in infertile patients approximately 3.5% and in patients with recurrent pregnancy losses approximately 13%. Septate uterus is the commonest uterine anomaly with a mean incidence of approximately 35% followed by bicornuate uterus (approximately 25%) and arcuate uterus (approximately 20%). It seem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
623
4
58

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 835 publications
(705 citation statements)
references
References 59 publications
20
623
4
58
Order By: Relevance
“…Almost all have double vagina-longitudinal vaginal septum. Incidence is 1 in 3000 [1]. Relatively uncommon it remains a challenge for the obstetrician especially at delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Almost all have double vagina-longitudinal vaginal septum. Incidence is 1 in 3000 [1]. Relatively uncommon it remains a challenge for the obstetrician especially at delivery.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] Risk factors for preterm birth include a history of preterm birth, [6][7][8][9][10][11][12] excisional treatment for cervical dysplasia [13][14][15] and presence of a uterine anomaly. [16][17][18][19] Cervical length measured by transvaginal ultrasonography has been shown to predict preterm birth in these asymptomatic high-risk women. 13,[20][21][22][23][24][25][26][27][28] Some studies have suggested that cervical length shortening by transvaginal ultrasonography may further increase the risk of preterm birth, 26,[29][30][31][32][33][34] whereas other studies have not noted this association.…”
Section: Introductionmentioning
confidence: 99%
“…1 We report a rare case in which placement of an intrauterine device (IUD) in 1 horn of a partially duplicated uterus resulted in a pregnancy in the other horn.…”
mentioning
confidence: 99%
“…The pregnancy outcome of patients with bicornuate uterus is poor, 2 with an abortion rate of 36%, preterm delivery rate of 23%, term delivery rate of 41%, and live birth rate of 55%. 1 In an unsuspected case of uterine duplication, if an IUD is placed in only 1 horn, it is possible to conceive in the other horn. Only 4 such cases have been reported in the literature.…”
mentioning
confidence: 99%